Gene action and combining ability studies for protein content and grain quality traits in rice (Oryza sativa L.) - M. Asvin Kirubha; R. P. Gnanamalar; K. Thangaraj; A. Kavitha Pushpam and; A. R. Priyanka (Electronic Journal of Plant Breeding, 2019)
Combining ability analysis was carried out with ten parents and twenty four F1’ s in Line × Tester mating design for the grain quality and nutritional traits viz., protein content, iron content and zinc content. The results showed that the dominance genetic variance is higher than that of additive genetic variance which indicated the predominance of non additive gene action for protein content, iron content, zinc content, hulling percentage, milling percentage, head rice recovery, kernel length, kernel breadth, kernel L/B ratio, linear elongation ratio, amylose content, gel consistency and gelatinization temperature whereas additive gene action was observed for kernel length after cooking. Among the lines, NLR 34449 was the best parent as it exhibited significant per se and gca effects for iron content, zinc content and important quality traits. In testers, CR Dhan 310 was found to be the best general combiner for protein content and Kodai for iron and zinc content which recorded highly significant positive gca effects. The hybrid ASD 16/ Kodai showed significant and desirable per se performance and sca effects for the nutritional traits viz., protein content, iron and zinc content. The hybrid RNR 15048/CB 14740 was adjudged as the best for the characters viz., kernel length, kernel L/B ratio, kernel length after cooking. These hybrids could be recommended for heterosis breeding to improve the nutritional and grain quality traits.